2013
DOI: 10.1007/s00737-013-0364-9
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the adolescent mother–infant relationship: preliminary trial of a brief perinatal attachment intervention

Abstract: The purpose of this study is to test a brief, attachment intervention added to routine maternity care that aims to improve the adolescent mother-infant relationship during transition to motherhood. A pre-test, post-test, peer-control-group trial was set in a large tertiary maternity hospital in Melbourne, Australia. Participants were multi-cultural, pregnant adolescents (n = 97). The two-session 'AMPLE' intervention was provided in late pregnancy and neonatally. The main outcome measure was mother-infant inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“… 77 By increasing parental sensitivity, the intervention also has the potential to positively affect biomarkers related to infant stress, as indicated by previous studies of attachment-based interventions. 78 However, research on the effect of NBO as a preventive intervention is scarce, and there is a need for more studies.…”
Section: Prevention and Treatment Of Ppdmentioning
confidence: 99%
“… 77 By increasing parental sensitivity, the intervention also has the potential to positively affect biomarkers related to infant stress, as indicated by previous studies of attachment-based interventions. 78 However, research on the effect of NBO as a preventive intervention is scarce, and there is a need for more studies.…”
Section: Prevention and Treatment Of Ppdmentioning
confidence: 99%
“…Relevant to this study, the shorter preventive interventions were actually more effective than the longer, more intensive programs. Similarly, Nicolson et al (2013) conducted a brief (2-session) intervention with adolescent mothers, and found that this was effective in enhancing several dimensions of emotional availability in the mother-child relationship.…”
Section: Discussionmentioning
confidence: 99%
“…La deuxième hypothèse est que les interventions optimisant le soutien maternel et les interactions mère-enfant sont les plus efficaces pour prévenir l'apparition de maltraitance chez les jeunes mères. Comme l'ajout d'une composante d'intervention basée sur l'attachement à un programme pour jeunes mères a déjà démontré des effets positifs sur la qualité de la relation mère-enfant et sur la disponibilité affective (Nicolson et al, 2013), il est possible de croire que ces effets positifs puissent aussi se traduire par un taux de maltraitance significativement plus faible.…”
Section: Objectifs Et Hypothèsesunclassified